2021
DOI: 10.3390/fluids6040146
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Propagation and Run-Up of Long Waves in U-Shaped Bays

Abstract: Wave propagation and run-up in U-shaped channel bays are studied here in the framework of the quasi-1D Saint-Venant equations. Our approach is numerical, using the momentum conserving staggered-grid (MCS) scheme, as a consistent approximation of the Saint-Venant equations. We carried out simulations regarding wave focusing and run-ups in U-shaped bays. We obtained good agreement with the existing analytical results on several aspects: the moving shoreline, wave shoaling, and run-up heights. Our findings also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The simulation result (Figure 4a) reveals that the velocity in the middle of the bay is faster than the shallow waters along the coast. This result is supported by previous studies that reported that Palu Bay bathymetry has a parabolic cross-sectional shape [28,29]. It has been understood based on previous research [23] that there are complex nonlinear interactions and energy transfers between ocean wind-waves and the mean flow.…”
Section: Model Of the Average Sea Surface Current Generated By Windsupporting
confidence: 85%
“…The simulation result (Figure 4a) reveals that the velocity in the middle of the bay is faster than the shallow waters along the coast. This result is supported by previous studies that reported that Palu Bay bathymetry has a parabolic cross-sectional shape [28,29]. It has been understood based on previous research [23] that there are complex nonlinear interactions and energy transfers between ocean wind-waves and the mean flow.…”
Section: Model Of the Average Sea Surface Current Generated By Windsupporting
confidence: 85%
“…where ∆Ē =Q −2/3 1 ∆Ê. Similarly to the one-layer shallow water model where steady hydraulics can be described as a trajectory of the energy curve, the steady interface of the two-layer model (assuming existence is guaranteed) can be described as a trajectory on the energy difference curve (17). This aspect will be discussed in detail by using specific examples in Sections 4 and 5.…”
Section: Formulation Using Normalized Variablesmentioning
confidence: 99%
“…The scheme can be used to solve problems with rapidly varying flows, such as those involving hydraulic jumps and bores. This scheme has been implemented and extended to various shallow water flow problems, such as in [10,16,17] where it was referred to as the MCS scheme, an abbreviation for the momentum conserving staggered-grid scheme. The extension of the MCS scheme to the two-layer model has been successfully used for the study of internal waves in [18].…”
Section: Numerical Modelmentioning
confidence: 99%
“…The outcomes of theoretical predictions for shallow-water waves were validated in the numerical modelling (see e.g. Vlasenko 1987;Choi et al 2008;Pudjaprasetya, Risriani & Iryanto 2021). The important feature of such solutions is that they describe the reflectionless wave propagation when the wave energy is transmitted most effectively through the inhomogeneous zone without energy losses on wave reflection.…”
Section: Introductionmentioning
confidence: 96%
“…Analytical solutions either in the exact or approximate forms are possible in exceptional cases; see e.g. Stoker (1957) and Sretensky (1977) in application to water waves. In these books, exact solutions for small-amplitude surface waves on water of arbitrary depth with a sloping bottom are presented.…”
Section: Introductionmentioning
confidence: 99%